4-Allyl-2-methoxyphenol modulates the expression of genes involved in efflux pump, biofilm formation and sterol biosynthesis in azole resistant Aspergillus fumigatus - Sen, Pooja; Gupta, Lovely; Vijay, Mukund; Vermani Sarin, Maansi; Shankar, Jata; Hameed, Saif; Vijayaraghavan, Pooja (Frontiers in Cellular and Infection Microbiology, 2023)
Antifungal therapy for aspergillosis is becoming problematic because of the toxicity of currently available drugs, biofilm formation on host surface, and increasing prevalence of azole resistance in Aspergillus fumigatus. Plants are rich sources of bioactive molecules and antimicrobial activity of aromatic bioactive compounds draws attention because of its promising biological properties. The present study elucidated the antibiofilm activity of 4-allyl-2-methoxyphenol (eugenol) against azole-resistant environmental A. fumigatus isolates. Soil samples were collected from agricultural fields across India; azole-resistant A. fumigatus (ARAF) were isolated followed by their molecular identification. Antibiofilm activity of eugenol was calculated via tetrazolium based-MTT assay. The expression of the multidrug efflux pumps genes MDR1, MDR4, transporters of the MFS gene, erg11A gene encoding 14α demethylase, and transcription regulatory genes, MedA, SomA and SrbA, involved in biofilm formation of A. fumigatus were calculated by quantitative reverse transcription PCR. Out of 89 A. fumigatus isolates, 10 were identified as azole resistant. Eugenol exhibited antibiofilm activity against ARAF isolates, ranging from 312 to 500 µg/mL. Confocal laser scanning microscopy analysis revealed absence of extracellular matrix of ARAF biofilm after eugenol treatment. The gene expression indicated significantly low expression of efflux pumps genes MDR1, MDR4, erg11A and MedA in eugenol treated ARAF isolates with compared to untreated isolates. Thus, our results demonstrate eugenol effect the expression of efflux pump and biofilm associated genes in azole resistant isolates of A. fumigatus. Hence, the findings conclude that eugenol inhibits biofilm formation of A. fumigatus and further investigations are warranted in this direction.